The Settlement of Children's Cases Through Diversion: Role of Leader Community for Justice - Lubis, Muhammad Ansori; Nurita, Cut; Sanni, Tajudeen (Unissula, 2025)
The prison punishment model makes law enforcement behavior only oriented towards punishment, so that the concept of diversion is only used as an option, without considering the importance of the success of its implementation, this study is expected to produce objectives to determine, analyze and study the role of the community in resolving cases of children in conflict with the law through diversion. This study used a socio-legal approach. The results of the study state that, Diversion, as part of restorative justice, aims to restore the condition of victims and perpetrators, and repair relationships damaged by criminal acts, not just to impose punishment. In addition, the issue of child criminal cases can also be resolved through non-formal mechanisms based on standard guidelines. Forms of non-formal handling can be carried out through diversion as a mediation process facilitated by law enforcement at every level. In the case of Children in Conflict with the Law, necessary to present community leaders to provide considerations for the success of diversion so that it achieves the value of justice.